Dataset for: "Knowing is half the battle: regulating and appraising emotions co-protect from suicidal ideation". - Mérida-López, Sergio; Quintana-Orts, Cirenia Luz; Pekaar, Keri A.; Pineda-Galán, Consolación; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
College students, particularly those in healthcare fields, face an elevated risk of suicidal ideation and depression. Therefore, it is essential to explore how both actual and perceived emotional resources may play a role in suicide prevention within this age group. This study examined (1) whether actual self-focused emotion-regulation ability diminishes suicidal ideation through a decrease in depressive symptoms, and (2) whether perceived self-emotion appraisal moderates this relationship. In 312 healthcare students (209 women) actual self- focused emotion-regulation ability was negatively related to suicidal ideation through depressive symptoms. Furthermore, perceived self-emotion appraisal buffered the relation- ship between depressive symptoms and suicidal ideation. Findings suggest that perceived self-emotion appraisal may reinforce the adaptiveness of actual self-focused emotion-regulation ability as a protective factor for psychological maladjustment. The results indicate the collaborative ability to regulate one’s emotions coupled with the self-perception of emotion appraisal could effectively alleviate the potential progression of emotional difficulties among healthcare students.
Database_Suicide_regulation_students.
Keywords: Inteligencia emocional; Suicidio - Factores de riesgo; Self-focused emotion regulation ability; Self-emotion appraisal; Depressive symptomatology; Suicide risk